(untitled) (Global Journal of Science Frontier Research, 2023)
The paper considers the possibility of optimizing the parameters of dispersion devices for gas analysis which use correlation reception of the useful signal and are used for the analysis of gas mixtures in the visible and UV regions of the spectrum The factors affecting the optimal filtering of the useful signal in the electronic path of the device are determined and methods of eliminating this influence including the background component of the signal are proposed As an example of the use of gas analysis devices with correlated selection of a useful signal in the electronic path of the analyzer the structural diagram of the device for the analysis of SO2 in the gases of thermal power plants is described